Compiler Research: the next 50 Years. - HALL, MARY; PADUA, DAVID; PINGALI, KESHAV (Communications of the ACM, 2009)
The article discusses research done in the area of computer compiler technology, which is defined as a computer program that translates a program written in a high-level language into another language, usually machine language. 2007 was the 50th anniversary of IBM's (International Business Machine's) release of the first optimizing compiler, the authors state. Topics include directions compiler technology make take from 2009 and beyond, a review of past contributions to compiler technology, and the status of compiler technology in 2009.